Wastewater Effluent from Outfalls in Kuwait Bay: A Threat to Recreational Water Quality - Ohoud Bushaibah , Adel Al-Haddad , Fatemah Dashti (Migration Letters, 2024)
The implications of wastewater discharge into marine ecosystems are gravely concerning due to their ability to trigger a chain reaction of contaminants that pose severe risks to both humans and aquatic life. Kuwait Bay is no exception, with numerous wastewater outfalls posing a threat to the marine environment on its southern coasts. This study sought to extensively evaluate the recreational water quality adjacent to wastewater outfalls at five specified sites and compare the results according to the KEPA’s (Kuwait’s Environmental Public Authority) guidelines. Field measurements and laboratory analyses were conducted to gauge various parameters associated with water quality, such as nutrients, heavy metals, fecal bacterial indicators (FBI), and pharmaceutical compounds. The results of field measurements indicated that two locations had insufficient DO levels with values < 4 mg/l below KEPA standards and brackish to saline water concerning Electrical conductivity (EC) measurements. However, the heavy metal results demonstrated mercury (Hg) pollution at all locations, whereas the nutrient data revealed significant PO4-P concentrations. Furthermore, EPA requirements were considerably exceeded for bacterial indicator counts (fecal coliforms, E. coli, and fecal streptococci), suggesting serious biological pollution at these locations and elevated concentrations of paracetamol and ranitidine have been detected in pharmaceutical compound analysis, particularly in location OC5. The study’s findings emphasized the significance of periodic surveillance to ensure the ongoing improvement of water quality and public health in Kuwait’s coastal zones and highlighted the dire need to address the extensive contamination by implementing measures to mitigate the dump of unprocessed wastewater into the sea.